The increase of philanthropic entities in the SUS: what does this scenario reveal? - Silva, João Felipe Marques da; Carvalho, Brígida Gimenez; Pereira, Adelyne Maria Mendes; Nunes, Elisabete de Fátima Almeida; Mendonça, Fernanda de Freitas; Santini, Stela Maris Lopes; Andrade, Silvia Karla Azevedo Vieira; Ferraz, Edinalva de Moura (Revista de Saúde Pública, 2023)
The article analyzes aspects of the change in the legal nature of private healthcare from “for-profit” to “non-profit” entities. It is an exploratory research, supported by the policy analysis framework, focusing on secondary data from the Cadastro Nacional de Estabelecimentos de Saúde (National R egistry of Health Facilities – C NES) f rom 2 012 t o 2 020 a nd a c ase s tudy. The results show an increase in these entities in all regions of the country and evidence that they behave like profit-oriented entities. The change in legal nature hides a broader process of implicit commodification of healthcare services, encouraged by state policies and related to exemptions provided by law.